Identification of lipase producing thermophilic bacteria from Malaysian hot springs - Hassan, Zuridah; N., Norazwin; M., Siti Aisyah; M. N. A., Fakhruzzaman; Allaudin, Zeenathul Nazariah (Academic Journals, 2011)
Lipase enzyme is an important group of biocatalyst for biotechnological application. One of the major industrial microorganism is the Bacillus species which are in abundance in the hot springs. The aim of this research was to isolate and characterize lipase producing bacteria from five hot springs in Malaysia. Eight bacterial strains from five hot springs were characterized by both biochemical and molecular techniques. Four strains were lipase producing thermophilic bacteria (coded as A1, A3, A4 and A14). The presence of lipase enzyme was confirmed by an orange fluorescence halos around the bacteria in rhodamine B olive oil agar plate. Based on molecular analysis, A1, A3 and A4 were assigned to the Bacillus and Geobacillus sp., and isolate A14 is found to be a nucleoside permease gene from Anoxybacillus flavithermus WK1.